2011
DOI: 10.1902/jop.2011.100472
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Interleukin‐1β Levels in Patients With Chronic Periodontitis Before and After Periodontal Phase I Therapy and Healthy Controls: A Case‐Control Study

Abstract: The data indicate that IL-1β levels are raised in the saliva of patients with chronic periodontitis, which are reduced after phase I therapy, suggesting a close association between salivary IL-1β and periodontitis. Additional longitudinal studies are needed to validate salivary IL-1β as a marker for periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 40 publications
(68 reference statements)
7
47
2
Order By: Relevance
“…In addition, the mediator panel in the Rathnayake study differed from ours, as was their statistical analysis. While we did not see a confounding effect of oral health on the associations between salivary profiles and asthma control in our study populations, others have found associations between certain inflammatory markers and oral health characteristics, including pocket depth, bleeding on probing [27], and periodontal disease status [28][30]. Further studies are warranted in asthmatics with a range of periodontal/gingival disease to definitively conclude that oral health does not confound associations between salivary marker profiles and asthma control.…”
Section: Discussioncontrasting
confidence: 63%
“…In addition, the mediator panel in the Rathnayake study differed from ours, as was their statistical analysis. While we did not see a confounding effect of oral health on the associations between salivary profiles and asthma control in our study populations, others have found associations between certain inflammatory markers and oral health characteristics, including pocket depth, bleeding on probing [27], and periodontal disease status [28][30]. Further studies are warranted in asthmatics with a range of periodontal/gingival disease to definitively conclude that oral health does not confound associations between salivary marker profiles and asthma control.…”
Section: Discussioncontrasting
confidence: 63%
“…Although it is not completely clear why two proinflammatory cytokines and a collagenase responded better to mechanical debridement than PGE 2 and MIP-1α, similar decreases in salivary concentrations of IL-1β and MMP-8 have been reported after phase I therapy in patients with chronic periodontitis. 33,42 One possible explanation is the potential role of PGE 2 in suppressing the release of IL-1β, IL-6, and TNF-α, 43,44 and these cytokines regulating the release of MMPs, which play a key role in degrading the extracellular matrix of connective tissue occurring in periodontal disease. 45 Thus, elevated levels of PGE 2 could be a protective mechanism to prevent the release of MMPs that would result in tissue breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…These cells, including resident fibroblasts and endothelial cells, can all synthesize and release IL-1β. Thus, genetic factors, local microbial quality, individual immunologic response, and activity of different combinations of inflammatory mediators may influence IL-1β levels [29]. …”
Section: Discussionmentioning
confidence: 99%